Land of dreams - Snelling, Lauraine; Giron, Kiersti (Home to Green Creek, 2025)
"Norwegian immigrant Amalia Gunderson and her ward, Ruth Forsberg, arrive in Iowa to claim the boardinghouse Ruth has inherited, despite opposition from a difficult cousin. While Amalia looks for her long-lost brother, her relationship with an attorney unfolds as she and Ruth navigate through love, loss, and unexpected friendships"--